Hubungan Antara Pengetahuan dan Sikap terhadap Pencegahan Penyakit Rabies - Arkian, Teobaldus Andrianus; Junias, Marylin Susanti (Universitas Pahlawan Tuanku Tambusai, 2025)
Rabies is a deadly disease that is transmitted through the bites of animals such as dogs, cats and several other animals. The high death rate due to rabies is often associated with a lack of public knowledge and attitudes towards preventing this disease. Therefore, public understanding and attitudes towards rabies are very important in efforts to prevent and control this disease. This study aims to determine the relationship between public knowledge and attitudes and rabies prevention measures. This research uses a simple literature review method. There is a significant relationship between public knowledge and attitudes and rabies prevention measures